Semantic-discursive study of responsibility in Paul Ricoeur (Revista Electrónica REDINE, 2023)
Human interaction revolves around discursive practices, whose semanticity is essential for the formation of culture. Through Discourse Analysis, it is possible to categorize, analyze, deconstruct and reconstruct discourses, whose relation with meaning and social bond is undeniable. This semantic-discursive study will review the category responsibility in the text Power, fragility and responsibility, a product of Paul Ricoeur's speech within the framework of his investiture as an honorary doctor by the Complutense University of Madrid in 1993. Two intentions are proposed: from the lexical-semantic point of view, to establish the meaning relation of the responsibility category, through the application of Van Dijk's macro-rules (cited by Calsamiglia and Tusón, 2001) to determine the global semantic macrostructure, the lexical and grammatical procedures that ensure the maintenance of the category and the metaphor analysis model proposed by Lakoff and Johnson (1995) as input to build concepts in the speech. From the discursive point of view, review the management of shared knowledge strategies (Van Dijk, 2013), which Ricoeur uses in front of the epistemic community of the Complutense University of Madrid, in order to guarantee communication, through presupposition and implicatures, which guide the understanding of the construction of knowledge of the extralinguistic world. It is concluded that the value of interdisciplinarity in language studies is due to the fact of articulating the structure of metaphor to the approach of shared sociocultural knowledge and ideology, which use discursive strategies to manifest them. Also, the lexical, semantic and discursive procedures used allowed us to specify the new definition of responsibility proposed by Ricouer, which enriches his ethical philosophy.
Keywords: Discourse analysis; relation of meaning; shared knowledge; responsibility; Ricoeur